Automatic selection of Dst storms and their seasonal variations in two versions of Dst in 50 years - Balan, N.; Tulasiram, S.; Kamide, Y.; Batista, I.S.; Souza, J.R.; Shiokawa, K.; Rajesh, P.K.; Victor, N. Jeni (My University, 2017)
A computer program is developed to automatically identify the geomagnetic storms in Dst index by applying four selection criteria that minimize non-storm-like fluctuations. The program is used to identify the storms in Kyoto Dst and USGS Dst in 50 years (1958–2007). The identified storms (DstMin ≤ −50 nT) are used to investigate their seasonal variations. It is found that the overall seasonal variations of the storm parameters such as occurrence, average intensity (average DstMin) and average strength (average ⟨DstMP⟩) in both versions of Dst exhibit clear semiannual variations with equinoctial maxima and solstice minima; and the maxima and minima in intensity and strength (~±17% each) are less than those in occurrence (~±28%). Wavelet spectra of the storms reveal the existence of distinct semiannual component in four solar cycles (SCs 20–23) and weak longer and shorter-period components in some SCs. The semiannual variation observed also in the mean energy input during the main phase (MP) of the storms estimated from Dst is interpreted in terms of the (1) equinoctial mechanism based on the varying angle between the Earth–Sun line and Earth’s dipole axis and (2) Russell–Mcpherron effect based on the varying angle between the GSM Z-axis and GSE Y-axis; and the yearly range of the dipole tilt angle μ (23.2°) involved in the equinoctial mechanism is found larger than the title angle θ (16.3°) involved in the RM effect.
Keywords: Geomagnetic Dst storms; Semiannual variation; Energy input; Ring current; Equinoctial hypothesis; RM effect